Pengelolaan Pembelajaran IPS Terpadu Di SMP Negeri 2 Miri Sragen - Suharso, Hery, Dr. Suyatmini, M.Si, Dr. Eko Supriyanto (2015)
This research aims are describe the planning, organizing, implementing, and evaluating of Integrated Social Sciences learning at SMP Negeri 2 Miri Sragen Academic Year 2013/2014. This research is qualitative research with case study design. Conducted in SMP Negeri 2 Miri Sragen. Data was collected by interview, observation and document. Data analysis technique used an interactive model of analysis. The results of this research are: 1) The planning of Integrated Social Sciences learning in junior high school include: preparation of the syllabus, preparation of the annual program (Prota), the preparation of the semester program (Promes), and the preparation of lesson plan (RPP). The uniqueness of integrated social studies lesson plan at Yunior High School State of 2 Miri is arranged in a region that last moment becoming a concern because of reports the location of Kemukus Mount. 2) Organizing Integrated Social Sciences learning at Yunior High School State of 2 Miri academic year 2013/2014 include: organizing syllabus, organizing prota, organizing promes, and organizing RPP. 3) Implementation of Integrated Social Sciences learning at Yunior High School State of 2 Miri academic year 2013/2014, includes introduction / apperception, core activities, and closing. The learning method used lectures, discussions, and assignments. 4) Evaluation of Integrated Social Sciences learning at Yunior High School State of 2 Miri academic year 2013/2014 conducted orally, written, and demonstration. Keywords: Management, Learning, Integrated Social Sciences.